The Development of an AppSheet-Based Digital Attendance System Using Integrated Technology to Support Student Discipline - Darojah Darojah; Nurkolis Nurkolis; Lilik Ariyanto; Milagros Racacho Baldemor (Research in Education, Technology, and Multiculture, 2026)
This study aims to design an AppSheet-based digital attendance application integrated with the Global Positioning System (GPS) and biometric features, and to evaluate the application's validity, practicality, and effectiveness. This study uses a research and development approach with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Data were collected through interviews, questionnaires, observations, and document analysis. Participants were students of SMP Negeri 2 Satu Atap Sluke in Rembang, Central Java, Indonesia, using multilevel and simple random sampling. Data analysis used expert validation tests and product practicality tests. The statistical analysis used was nonparametric statistics because the number of samples was small and no immersion test was carried out, consisting of the Wilcoxon test and the Spearman correlation test. In addition, an N-Gain test was conducted. The results of the study showed that the developed instrument had very good validity (98%), so it could be used. The practicality test showed a score of 92%, indicating that this product is very practical to use. The effectiveness of this product was evaluated using three types of tests: the Wilcoxon test, Spearman's correlation, and the N-Gain. The Wilcoxon test showed that digital attendance significantly increased student attendance (p = 0.001 0.05), by 8 points compared to manual attendance. The Spearman's rho showed no significant difference in the use of this digital attendance system in improving student discipline, with a significance value of 0.176 0.05. The N-Gain showed an average value of 0.04, indicating a low increase. It is recommended that the use of digital attendance to improve student discipline not be left solely to the device, but also receive support from various stakeholders, such as teachers, principals, parents, and the community. Keywords: digital attendance system; student discipline; GPS technology; biometric technology; appsheet-based.